Gestión de Tecnologias de Información - SI710 - 202301 - Mejía Tarazona, Ronald (2023)
The course explains the fundamentals of IT Service Management, how IT Service Management influences the achievement of business objectives and, based on the ITIL 4 methodological approach, develops a proposal of the implementation that an IT organization should carry out to maximize the value in the delivery and support of its technology services.